Impact responses of sandwich panels with fibre metal laminate skins and aluminium foam core. (15th December 2017) - Liu, Chengjun; Zhang, Y.X.; Li, Jing
Abstract: Low velocity impact responses of a newly developed sandwich panel with aluminium foam core and fibre metal laminate (FML) skins, comprised of aluminium sheets and plain woven E glass fibres, are investigated in this paper. Drop weight impact tests were conducted and the effect of the thickness of foam core and FML skin on the impact response of the panels was investigated via the experimental study. A finite element model is also developed and validated against the experiments to prove the effectiveness and accuracy for analyzing the impact responses of the sandwich panels under low-velocity impact. The research findings are summarized and concluded finally.